Characteristics and risk assessment of organophosphate esters and phthalates in soils and vegetation from Dalian, northeast China. (1st September 2021) - Wang, Yan; Zhang, Zihao; Bao, Meijun; Xu, Yue; Zhang, Lijie; Tan, Feng; Zhao, Hongxia
Abstract: We investigated the concentration, composition, and potential risk of organophosphate esters (OPEs) and phthalates (PAEs) in soils and vegetation from rural areas of Dalian, Northeast China. The residues of total OPEs and PAEs in soils were in the range of 33.1–136 ng/g dw (dry weight) and 465–5450 ng/g dw, while the values in plants were 140–2360 ng/g dw and 2440–21800 ng/g dw, respectively. The concentrations of both chemicals in the plant rhizosphere soils were significantly lower than those in the bulk soils, suggesting an enhanced degradation or uptake by plant. The contaminations in soils also varied for different land use types with the concentrations generally higher in paddy soils than those in maize soils. The OPE and PAE concentrations in plant leaves were slightly higher than those in their corresponding roots. The bioconcentration factors of OPEs & PAEs were significantly negatively correlated with their octanol-water partition coefficients. A hazard assessment suggested potential medium to high risks from tricresyl phosphate (TMPP) and di- n -butyl phthalate (DNBP) for the agricultural soils in Dalian of China. Although the ecological risks of OPEs and PAEs in the rhizosphere soils were lower than those in the bulk soils, the relevant risk could still endanger human health via oral intake of these plants. The daily dietary intakes of OPEs and PAEs via vegetable and rice consuming were estimated, and the result suggests a higher exposure risk via ingestion of leafy vegetable than rice. Graphical abstract: Image 1 Highlights: Relatively high OPEs and PAEs were found especially in paddy and vegetable soils. OPEs and PAEs were generally higher in the rhizosphere soil than in the bulk soils. Bioconcentration of OPEs & PAEs was negatively correlated with their K ow values. Potential medium to high risks from TMPP and DNBP were found for agricultural soil.